Effects of Nitrogen Fertilizer Quantity and Time of Application on Sorghum (Sorghum bicolor (L.) Moench) Production in Lowland Areas of North Shewa, Ethiopia - Degu Temeche; Elias Getachew; Gtachew Hailu (International Journal of Agronomy)
This research was conducted to assess the effect of rates and time of nitrogen fertilizer application on yield and yield components of sorghum in lowland areas of North Shewa. The treatments contained three rates of nitrogen (N) (46, 92, and 138 kg·ha−1) and three times of N application (1/2 dose at sowing and 1/2 dose at tillering (timing one); 1/3 dose at sowing and 2/3 dose at tillering (timing two); and 1/3 dose at sowing, 1/3 dose at early tillering, and 1/3 dose at tillering (timing three) including one control. Days to 50% maturity, plant height, head length, head weight, and grain yield were significantly affected by treatment effect, while days to emergency, days to heading, and thousand kernel weight showed nonsignificant effect. The maximum grain yield was 5.060, 5.169, 5.836, and 5.555 t·ha−1 from T2, T5, T8, and T10, respectively, and statistically similar yield was recorded at combination of different rates in two split applications (1/2 dose at sowing and 1/2 dose at tillering). By considering the economic status of the farmers, the applications of 46 kg·N·ha−1 in two split doses (1/2 dose at sowing and 1/2 dose at tillering stage) gave 87,122 Birr·ha−1 with a MRR of 475.61%, which gave best economic benefit. Therefore, it can be concluded that use of 46 kg·N·ha−1 in two split applications (1/2 dose at sowing and 1/2 dose at tillering stage) can be recommended for farmers for production of sorghum in the study area and other areas with similar agroecological conditions.